The use of multiple textual forms in distance learning - Cynthia White (Flexible Learning Association of New Zealand, 2012)
This article reports on a study of how students perceive, access and evaluate the different textual forms which comprise a distance education course. The setting for the study was an introductory distance programme in Spanish, using print, aural and visual media. Thirty one students completed a self-report questionnaire which investigated the following aspects of the use of multiple textual forms: primary vs. secondary sources, preferences for initial input, intertextual links, time allocation, source evaluation. Findings revealed a consistent pattern in terms of conceptions of primary vs. secondary sources: in particular, the study guide was consistently judged to be central to the course, more so than other print, visual or aural sources. Students' reported behaviour when embarking on a new unit revealed a distinct preference for either verbal or visual input, each providing a qualitatively different orientation to the unit. Intertextual links characterised the way students worked with the multiple texts: it was possible to identify two 'anchor' texts, which acted as the base texts and were supplemented by other sources. Responses of students highlighted the importance of multiple texts for learning, largely because of their complementary nature, the 'relief' they provide and opportunities for students to establish their own learning paths. The article concludes with a view of the learner not as a course consumer but as a course developer, creating texts and intertexts through engagement with multiple sources.